Neurofeedback for Moral Enhancement: Irreversibility, Freedom, and Advantages Over Drugs - Maslen, H; Savulescu, J (Taylor and Francis (Routledge), 2016)
Nakazawa and colleagues(2016) examine potential therapeutic applications of decoded neurofeedback for the treatment of psychiatric conditions such as depression, and developmental disorders. While we agree that adverse side effects and efficacy are clearly relevant to the ethical assessment of neurofeedback for the full range of potential purposes, we challenge the authors' claim that the irreversibility of the effects of neurofeedback necessarily presents a problem for its use for moral enhancement.